Status dan Legalitas Hukum Perdata Internasional Terhadap Perkawinan Campuran Antara WNI dengan Imigran Ilegal (RechtJiva, 2025)
Mixed marriages between Indonesian citizens and illegal immigrants occurring in Indonesia are related to foreign elements because these marriages involve Indonesian citizens and foreign parties whose personal status is unknown, resulting in incomplete norms in Article 16 AB regarding personal status, which states that wherever an Indonesian citizen is located, national law still applies. This study aims to analyze the applicable law in mixed marriages between Indonesian citizens and illegal immigrants, as well as to analyze the applicable law in mixed marriages between illegal immigrants and illegal immigrants in Indonesia. This study uses normative legal research with a regulatory approach, an analytical approach, and a case approach. There are three types of legal materials, namely primary, secondary, and tertiary legal materials, with legal material analysis techniques, namely grammatical interpretation and systematic interpretation. The results of this study are based on the provisions of International Civil Law, which uses the principle of nationality. This principle cannot be used by illegal immigrants who are known to have no citizenship. Articles 13, 15, 16, and 17 of the HPI Bill state that the applicable principle is the principle of nationality in the principle of domicile, with the provision that the person has lived in Indonesia for 5 consecutive years or 10 non-consecutive years. However, if an illegal immigrant has been granted refugee status by the UNHCR, Article 35(b) of the Population Administration Law states that marriages between foreign nationals in Indonesia may be registered. However, this provision cannot be applied to illegal immigrants who marry in Indonesia because there is no connection between the two.